1995
DOI: 10.1002/1097-0142(19951115)76:10+<1888::aid-cncr2820761305>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of cervical carcinogenesis

Abstract: Epidemiologic and laboratory data suggest that cervical cancer typically arises from a series of causal steps. Each step can be studied separately in the hope of better etiologic understanding and improved cancer prevention. The earliest identified etiologic step is infection of young women with specific types of venereally transmissible human papillomaviruses (HPVs). Cervical HPV infections often lead to low grade squamous intraepithelial lesions (mildly abnormal Pap smears). Human papillomavirus infections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
170
1
12

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(193 citation statements)
references
References 131 publications
5
170
1
12
Order By: Relevance
“…Causal models that have been proposed are trauma to the cervix or hormonal effects (Schiffman and Brinton, 1995). Since very few women in our study were multiparous, we investigated a possible effect of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Causal models that have been proposed are trauma to the cervix or hormonal effects (Schiffman and Brinton, 1995). Since very few women in our study were multiparous, we investigated a possible effect of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…1 Infection by highrisk human papillomavirus (HPV) is a major cause of CACX 2 along with other etiological factors, such as use of oral contraceptives, precocious marriage, multiparity and smoking. 1,3 As HPV infections in most cases do not lead to cancer, and even a long latency period for the cancerous outcome in infected women suggests involvement of additional genetic alterations like functional inactivation of tumor suppressor genes (TSGs) or activation of oncogenes. 4 Investigations showing frequent chromosomal deletion in 11q23-q24 (20.4 Mb) in cervix, 5-7 breast, 8,9 lung, 10 colon 11 and ovarian 12 cancer and functional chromosome-transfer…”
mentioning
confidence: 99%
“…But neither research assays nor commercial kits (dot blot or in situ hybridization) have been found to be adequate for clinical use. An assay for routine clinical use requires reliable and accurate detection of the broad range of pathogenic HPV types that infect the genital tract [5].…”
mentioning
confidence: 99%
“…In many developing countries, it is still the main cause of death from cancer in women [5]. High annual cancer incidences have been reported in Brazil.…”
mentioning
confidence: 99%